2013
DOI: 10.1111/ctr.12159
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of enhanced systemic inflammation in stable kidney transplant recipients with low Framingham risk scores

Abstract: Over one half of stable RTR, including those with low FRS, have increased inflammatory chemokine levels. Inflammation is not accounted for in the FRS, and this may explain the poor performance of FRS in transplant patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 42 publications
1
8
0
2
Order By: Relevance
“…This explanation is supported by other researchers, who have documented an increase in cardiovascular risk in patients with renal dysfunction (7,8,19). It is also consistent with our previous work, where we observed that impaired renal function was strongly associated with an increase in inflammatory markers, but no relationship was evident between these variables and FRS (25).…”
Section: Discussionsupporting
confidence: 93%
“…This explanation is supported by other researchers, who have documented an increase in cardiovascular risk in patients with renal dysfunction (7,8,19). It is also consistent with our previous work, where we observed that impaired renal function was strongly associated with an increase in inflammatory markers, but no relationship was evident between these variables and FRS (25).…”
Section: Discussionsupporting
confidence: 93%
“…After a successful renal transplant, the patient’s risk of having a cardiovascular events diminishes, but remains elevated compared to the general population. This is in part due to enhanced circulating chemokine ligand levels [19]. …”
Section: Introductionmentioning
confidence: 99%
“…Some interleukins were elevated in both patient subgroups (high and low-risk) above control values. They likely contribute to the known systemic inflammatory burden, which is increased in transplantation [ 13 ]. In this study we noticed elevated levels of IL-6, IL-8, IL-9, IL-17 and IL-33 in the high risk group.…”
Section: Discussionmentioning
confidence: 99%